Nursing documentation and its relationship with perceived nursing workload: a mixed-methods study among community nurses - Kim De Groot; Anke J. E. De Veer; Anne M. Munster; Anneke L. Francke; Wolter Paans (BMC, 2022)
Abstract Background The time that nurses spent on documentation can be substantial and burdensome. To date it was unknown if documentation activities are related to the workload that nurses perceive. A distinction between clinical documentation and organizational documentation seems relevant. This study aims to gain insight into community nurses' views on a potential relationship between their clinical and organizational documentation activities and their perceived nursing workload. Methods A convergent mixed-methods design was used. A quantitative survey was completed by 195 Dutch community nurses and a further 28 community nurses participated in qualitative focus groups. For the survey an online questionnaire was used. Descriptive statistics, Wilcoxon signed-ranked tests, Spearman's rank correlations and Wilcoxon rank-sum tests were used to analyse the survey data. Next, four qualitative focus groups were conducted in an iterative process of data collection - data analysis - more data collection, until data saturation was reached. In the qualitative analysis, the six steps of thematic analysis were followed. Results The majority of the community nurses perceived a high workload due to documentation activities. Although survey data showed that nurses estimated that they spent twice as much time on clinical documentation as on organizational documentation, the workload they perceived from these two types of documentation was comparable. Focus-group participants found organizational documentation particularly redundant. Furthermore, the survey indicated that a perceived high workload was not related to actual time spent on clinical documentation, while actual time spent on organizational documentation was related to the perceived workload. In addition, the survey showed no associations between community nurses' perceived workload and the user-friendliness of electronic health records. Yet focus-group participants did point towards the impact of limited user-friendliness on their perceived workload. Lastly, there was no association between the perceived workload and whether the nursing process was central in the electronic health records. Conclusions Community nurses often perceive a high workload due to clinical and organizational documentation activities. Decreasing the time nurses have to spend specifically on organizational documentation and improving the user-friendliness and intercommunicability of electronic health records appear to be important ways of reducing the workload that community nurses perceive.